Sustainability and property: A legal perspective - Klaus Bosselmann (Global Journal of Ecology - Peertechz Publications, 2023)
Property and sustainability both represent strongly felt concepts of society but in very different ways. While the protection of the individual property is at the heart of the capitalist system and deeply embedded in our laws, concerns for ecological sustainability feature less prominently and only indirectly impact private property. Critically, the integrity of Earth's ecological systems is hardly protected at all. Environmental laws in the world over-regulate the use and protection of natural "resources" in a strict instrumental fashion and tend to take the integrity of Earth's ecological systems for granted.  This article explores some of the histories of environmental law, sustainability and property in the European context. It then shows how ecological sustainability can shape the content and scope of the private property using some examples in New Zealand and Germany. The overall thesis is that both concepts can be reconciled on the basis of ecological integrity as a fundamental norm of law.